Potret Islam di Kasultanan Yogyakarta Abad XVIII: Kajian Terhadap Penulis Naskah Babad Kraton - Maharsi Maharsi (Jurnal Lektur Keagamaan, 2017)
This paper reveals a religious practice as observed in the Yogyakarta Sultanate in the XVII century through the lense of of Babad Kraton. The writer of Babad Kraton, who is a Javanese aristocrat, attempts to reveal Islamic practices that he does based on his life experience and environment. In this study of the manuscript, this research uses the method of Philology research to get the best available text and worthy of study to be used as research material. The results of this study show that the author of Babad Kraton shows his great love of knowledge and devotion to God. It is clear that the text of Babad Kraton contains Islamic values that are adapted to the Javanese cultural background. Islamic treasures that appear in the text of Babad Kraton are also expected to perfect and validate the existence of the Sultan's Palace as an Islamic Kingdom in Java. Keyword: Islam, Java, Yogyakarta Sultanate, Babad Kraton Tulisan ini mengungkapkan paktek keagamaan di Kasultanan Yogyakarta pada abad XVII melalui Penulisan Naskah Babad Kraton. Penulis Naskah Babad Kraton yang merupakan bangsawan Jawa berupaya mengungkapkan praktek keIslaman yang dilakukannya berdasarkan lingkungan kehidupannya. Sebagai sebuah kajian naskah, penelitian ini menggunakan metode penelitian Filologi untuk mendapatkan teks yang paling baik dan layak digunakan sebagai bahan kajian. Hasil kajian ini menunjukkan bahwa penulis Babad Kraton menunjukkan cintanya yang sangat besar terhadap ilmu dan baktinya kepada Allah swt. Teks Babad Kraton mengandung nilai-nilai keislaman yang disesuaikan dengan latar belakang budaya Jawa. Khazanah keislaman yang dimunculkan dalam teks Babad Kraton juga diharapkan untuk menyempurnakan dan mensahkan eksistensi Kraton Yogyakarta sebagai Kerajaan Jawa Islam. Kata kunci: Islam, Jawa, Kasultanan Yogyakarta, Babad Kraton